1994
DOI: 10.1007/bf00666153
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptors in breast cancer cells

Abstract: 1,25-(OH)2-Vitamin D3, the active metabolite of vitamin D, is a secosteroid hormone with known differentiating activity in leukemic cells. Studies have demonstrated the presence of vitamin D receptors (VDR) in a wide range of tissues and cell types. Antiproliferative activity of 1,25-(OH)2-vitamin D3 has been documented in osteosarcoma, melanoma, colon carcinoma, and breast carcinoma cells. This study was designed to analyze vitamin D receptor level in breast cancer cells as a marker of differentiation and as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
66
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 46 publications
9
66
0
3
Order By: Relevance
“…De demonstrerte hvordan kalsitriol hemmer celledeling og øker differensieringen av kreftceller. Flere eksperimentelle studier viser at kalsitriol også fremmer celledød og hemmer tumorvekst (16,(20)(21)(22)(23). Epidemiologiske studier viser at forekomsten og dødeligheten av kreft i bryst, prostata og tykktarm er større i nord sammenlignet med i sør, og man tror at forskjeller i UVeksponering og i vitamin D-nivå kan forklare disse resultatene (24)(25)(26)(27)(28).…”
Section: Vitamin D Og Kreftunclassified
See 1 more Smart Citation
“…De demonstrerte hvordan kalsitriol hemmer celledeling og øker differensieringen av kreftceller. Flere eksperimentelle studier viser at kalsitriol også fremmer celledød og hemmer tumorvekst (16,(20)(21)(22)(23). Epidemiologiske studier viser at forekomsten og dødeligheten av kreft i bryst, prostata og tykktarm er større i nord sammenlignet med i sør, og man tror at forskjeller i UVeksponering og i vitamin D-nivå kan forklare disse resultatene (24)(25)(26)(27)(28).…”
Section: Vitamin D Og Kreftunclassified
“…Både de eksperimentelle og epidemiologiske studiene indikerer at vitamin D kan hemme progresjon av visse kreftformer og at et høyt vitamin D-nivå kan bedre prognosen ved en kreftsykdom. Det er også studier som indikerer at vitamin D samvirker med og øker effekten av strålebehandling og dermed øker overlevelsen ved kreftsykdom (21,30).…”
Section: Vitamin D Og Kreftunclassified
“…Freake et al (6) found that, in human breast tumor cells, VDR expression is at concentrations higher than previously described, and Bu-ras et al (13) reported that high VDR expression is seen in well-differentiated tumors as compared with less differentiated tumors.…”
mentioning
confidence: 95%
“…Earlier, the VDR was found to be present in abundance in intestine, bone, liver, and kidney cells. Aside from the classical target organs, the VDR has now been isolated from a variety of tissues including normal mammary epithelium as well as breast tumors (Buras et al, 1994;Eisman et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, the VDR was found to be present in abundance in intestine, bone, liver, and kidney cells. Aside from the classical target organs, the VDR has now been isolated from a variety of tissues including normal mammary epithelium as well as breast tumors (Buras et al, 1994;Eisman et al, 1980).In order for VDR to function, it needs to interact with vitamin D response elements (VDRE) and bind to DNA to initiate or repress transcription . VDR must form a dimer to stabilize VDRE transactivation (Jones et al, 1998).…”
mentioning
confidence: 99%